Impact of age, sex, and joint form on degenerative lesions of the sacroiliac joints on CT in the normal population - Katharina Ziegeler; Virginie Kreutzinger; Torsten Diekhoff; Robert Roehle; Denis Poddubnyy; Matthias Pumberger; Bernd Hamm; Kay Geert A. Hermann (Scientific Reports, 2021)
Abstract Degeneration of the sacroiliac joints (SIJs) is a common finding, while its underlying cause and development remain incompletely understood. The aim of this investigation was to describe the spatial distribution of degenerative SIJ changes across age groups and to investigate for the first time their relationship to anatomical form and sex. For this IRB-approved investigation, demographic data of 818 patients without SIJ disease were retrieved from electronic patient records. High-resolution computed tomography (CT) datasets of all patients were analysed retrospectively for seven predefined age groups (ten-year increments, from < 25 to ≥ 75). A structured scoring system was applied to assess sclerosis, osteophytes, joint space alterations, and anatomical form. Chi-square tests were used to compare frequencies of degenerative lesions, and logistic regression analyses were performed to investigate associations between demographic data, anatomical form, and the presence of structural lesions. Sclerosis and osteophytes were common findings, with an overall prevalence of 45.7% and 46.8%, respectively. Female sex had an odds ratio (OR) of 0.15 (95% CI: 0.08–0.27) for the presence of ventral osteophytes and of 4.42 (95% CI: 2.77–7.04) for dorsal osteophytes. Atypical joint forms were significantly more prevalent in women with 62.1% vs. 14.1% in men (p < 0.001). Accessory joints increased the likelihood of dorsal sclerosis (OR 2.735; 95% CI 1.376–5.436) while a typical joint form decreased its likelihood (OR 0.174; 95% CI 0.104–0.293). Sex and anatomical joint form have a major impact on the development of degenerative lesions of the SIJs and their spatial distribution.